STUDY ON THE LOAD ASSESSMENT METHOD AND DEVELOPMENT OF THE LOAD ASSESSMENT PROGRAM FOR THE TAIL SUPPORT DEVICE OF THE FL-17 WIND TUNNEL - ZHAO Yu; CAO QingYuan; WU SongLing; YANG BenChuan; ZHAO Kun; YIN XiWei (Jixie qiangdu)
The loads applied on the driving hydraulic cylinders, attack angle joint bearings and sideslip angle joint bearings in the tail support device of the FL-17 wind tunnel were deduced using a coordinate transformation approach. The load vectors applied on these components were obtained in closed form. A load assessment program with graphical user interface was developed using MATLAB. The safety coefficients of the driving hydraulic cylinders and the bearings can be readily calculated by importing the structural parameters and inputting the load parameters. The shortages of high computational cost and low assessment efficiency of the multi body dynamics simulation is overcame. Taking the example of a wind tunnel test, the developed method and program is applied to verify the strength of the tail support device and the results indicate that the tail support device is sufficient to perform the wind tunnel test. The present work provides a method with high accuracy and efficiency for the preparation and argument for wind tunnel tests and has significant practical value.